A Killer carol - Bradford, Laura (Bradford, Laura. Amish mystery., 2019)
"Heavenly, PA has been transformed into a Christmas wonderland, and Claire is delighted to celebrate the season...but a fiendish killer has other plans.--Page 4 of cover